Factors Influencing the Burden of Family Caregiving for Survivors of Stroke - Boonsin, Suneerat; Deenan, Aporn; Wacharasin , Chintana (Pacific Rim International Journal of Nursing Research, 2020)
Family caregivers undertake roles to assist survivors of stroke in all life aspects. However there are burdens for family caregivers brought on by their duties and responsibilities and difficulties related to life changes and adjusting to their new roles. In this cross-sectional, model testing study the aim was to examine factors influencing burden among family caregivers of survivors of stroke, during the first six months after stroke. A convenience sample of 200 caregivers of survivors of stroke from two hospitals in Central Thailand was recruited. Six instruments were used, including one to gather demographic data of survivors of stroke and caregivers, the Zarit Burden Interview, the Health Perception Scale, the Barthel Index, the General Perceived Self-Efficacy Scale, and the Revised Multi-dimensional Scale of Perceived Social Support. Descriptive statistics and structural equation modeling by AMOS were used to analyze data. Results found that the final model of caregiving consisted of functional status of survivors of stroke, duration of care giving, self-efficacy, and number of hours of care with total variance explained 39%. Functional status and duration of care giving had direct and indirect effects on burden. Hours of care mediated functional status and caregiver burden, whereas self-efficacy mediated both functional status and duration of care giving and caregiver burden. Assessment for family caregiver burden prior to patient hospital discharge is essential. Nurses might consider innovative approaches to care, such as partnering with multidisciplinary team to develop online / mobile apps that families may access for current evidence in caregiving, practical tips for reducing burden, and enhancing self-efficacy through virtual support groups.